Van hiele ideas and the realistic mathematical education: A few approximations - Passos, Adriana Quimentão; de Buriasco, Regina Luzia Corio [UNESP]; Soares, Maria Tereza Carneiro (FapUNIFESP (SciELO), 2019)
This article originated in a research that investigated possible relations between the principles of Realistic Mathematical Education assessment and the learning process phases proposed by Dina Van Hiele-Geldof and Pierre Van Hiele, seeking approaches. The work was developed in a research perspective of theoretical nature, of the speculative type. It highlights the educational aspect of Van Hiele's work, in particular, the learning process phases: information, guided guidance, exploitation, free orientation, and integration. It considers that the learning process phases of Van Hiele's approach are another auxiliary element in the elaboration of mathematical knowledge from situations that can be mathematized, developed through a guided reinvention process based on information collected in assessment situations.
Ideias de Van Hiele e Educação Matemática Realística: Algumas aproximações
Keywords: Assessment Principles; Mathematics Education; Realistic Mathematics Education; Van Hiele